Physiolgic hypercortisolism at onset of celiac disease in a girl: A case report - Esposito, Susanna (Medicine (Baltimore), 2018)
RATIONALE: Celiac disease (CD) is an autoimmune disorder induced by dietary gluten in genetically predisposed subjects. Activation of the hypothalamic-pituitary-axis (HPA) can occur in patients with CD; however, this condition has never been described in overweight/obese CD children. PATIENT CONCERNS: A 12-year-old girl with CD was admitted with mild acanthosis nigricans of the armpits, groin and neck. Recently, extra fat appeared around the neck, and moon face was observed. The abdomen was globular and meteoric, treatable and not aching. She weighed 64 kilos (75°–97° percentile) and was 146 centimeters tall (3°–25° percentile) with a body mass index of 30 kg/mq(2). Laboratory tests revealed hypertriglyceridemia and positive anti-transglutaminase IgA. Cortisoluria was determined. Serum ACTH was normal. DIAGNOSES: This paper reports a case of a girl with CD in which both obesity and activation of HPA activity were noted. INTERVENTIONS: During follow-up, anti-transglutaminase IgA increased to 201.5 UI/mL. The patient was positive for anti-endomysium antibodies, and the HLA DQ2 haplotype was identified, confirming a diagnosis of CD. OUTCOMES: Despite a gluten-free diet, obesity and hyperadrenalism persisted, and anti-transglutaminase antibodies remained elevated. In addition, high cortisoluria persisted. A high-dose suppression dexamethasone test (8 mg) produced negative results with a morning cortisol value of 1 ng/mL, suggesting the diagnosis of pseudo-Cushing's syndrome. LESSONS: This case highlights that the first manifestation of CD could be being overweight, and this finding seems to support the need to prescribe laboratory tests for CD not only to children with failure to thrive, as commonly recommended, but also to those with increased body weight.